Konstitusionalitas Fungsi dan Wewenang Wakil Presiden RI Setelah Amandemen UUD 1945 - Johannes Johny Koynja (Jatiswara, 2015)
This article represent effort to reflect again how far the 1945 Constitution of the Republic of Indonesia have guaranteed constitutionality function and authority of Vice President of Republic of Indonesia as "assistant" President which still there are dimness or ill defined norm (vague van normen) and also continuous to become polemic. The 1945 Constitution of the Republic of Indonesia do not give clear arrangement, adequate and coherent about how in fact form relation mechanism work and division of authority between Presidents with Vice President which have been elected as a single ticket directly by the people, considering that Vice President is "partner which is image" with President because both have been elected as a single ticket directly by the people. Including the Article 4 Paragraph 2 the 1945 Constitution of the Republic of Indonesia does not give interpretation of authentic concerning term "The President shall be assisted by a Vice President".